Spanish academic writing for aerospace engineering students - Dolzhich, Elena; Dmitrichenkova, Svetlana (Edelweiss Applied Science and Technology, 2025)
In the contemporary landscape of international academic communication and research, it is essential to consider how to instruct both undergraduate and graduate aerospace engineering students learning Spanish as a second language in the art of writing research papers. The paper deals with the analysis of aerospace technical texts’ structure and design in Spanish. The research base consists of original open-access papers on aerospace engineering published from 2018 to 2024. Since there is a clear lack of such teaching materials in the Spanish language, the issue is of significant relevance. The purpose of this paper is to analyze the structure of aerospace technical texts, to reveal the sequence of scientific knowledge presentation and its corresponding connectors, and to provide practical recommendations for undergraduate and graduate students. The findings suggest that: (1) the structural units of the text reflect the stages of the researcher’s cognitive activity; (2) an aerospace technical text is a logical chain of the author’s ideas, based on previous knowledge and cognitively related to their findings, with an outlook for future research; and (3) each text unit, understood as a structural element, has specific connectors within the text. This paper identifies text structural units designed to construct a comprehensive model of the aerospace technical text and provides appropriate Spanish connectors for each. The primary research methods employed include a structural analysis approach and a descriptive method, utilizing techniques such as observation, interpretation, and generalization. The findings offer practical solutions to improve engineering students’ academic writing, which can be applied to teaching processes or to enhance current instructional approaches.